Polymorphism of mtDNA Cytochrome b Gene of Local Cattle in Indonesia - Tety, Hartatik (2015)
The aim of this study was to evaluate of genetic diversity of local cattle in Indonesia. We analyzed the polymorphism of mtDNA cytochrome b (cytb) gene using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) method. Seventy-three Indonesian local cattle were used in the study that consisted of Madura cattle from Madura island (n = 15), Madura cattle from Sapudi island (n = 23), Limousin x Madura from Madura island (n = 5), Bali cattle from Kupang (n = 12), Aceh cattle from Aceh (n = 5), Pesisir cattle (n = 4), Bali cattle from West Sumatera (n = 1), and Java cattle from Pacitan (n = 8). The 464-bp fragment of cytochrome b (cyt b) gene was amplified using primers: forward primer of L14735 and reverse primer of H15149. The PCR product was digested using HinfI and TaqI restriction enzyme to identify the polymorphism of mtDNA cytochrome b (cytb) gene. The result showed that there was two haplotypes (A and B). Aceh and Pesisir cattle have 100% haplotype B meanwhile Bali cattle (from Kupang and West Sumatera) and Limura cattle have 100% haplotype A. Whereas, Madura cattle from Madura and Sapudi island and Java cattle have two different haplotypes (A and B). There was mt-DNA cytochrome b polymorphism of local cattle in Indonesia based on PCR-RFLP analysis method. Since the genetic variation in local cattle showed the differences in the specific area, it is necessary to control the cattle populations based on the species.